Unusually High Optical Transparency in Hexagonal Nanopatterned Graphene with Enhanced Conductivity by Chemical Doping. Issue 26 (31st March 2015) - Choi, Duyoung; Kuru, Cihan; Choi, Chulmin; Noh, Kunbae; Hwang, Sookhyun; Choi, Wonbong; Jin, Sungho
<x xml:space="preserve">Abstract</x> Graphene has received appreciable attention for its potential applications in flexible conducting film due to its exceptional optical, mechanical, and electrical properties. However increasing transmittance of graphene without sacrificing the electrical conductivity has been difficult. The fabrication of optically highly transparent (≈98%) graphene layer with a reasonable electrical conductivity is demonstrated here by nanopatterning and doping. Anodized aluminium oxide nanomask prepared by facile and simple self‐assembly technique is utilized to produce an essentially hexagonally nanopatterned graphene. The electrical resistance of the graphene increases significantly by a factor of ≈15 by removal of substantial graphene regions via nanopatterning into hexagonal array pores. However, the use of chemical doping on the nanopatterned graphene almost completely recovers the lost electrical conductivity, thus leading to a desirably much more optically transparent conductor having ≈6.9 times reduced light blockage by graphene material without much loss of electrical conductivity. It is likely that the availability of large number of edges created in the nanopatterned graphene provides ideal sites for chemical dopant attachment, leading to a significant reduction of the sheet resistance. The results indicate that the nanopatterned graphene approach can be a promising route for simultaneously tuning the optical and electrical properties of graphene to make it more light‐transmissible and suitable as a flexible transparent conductor.